2016
DOI: 10.1021/acs.langmuir.6b02952
|View full text |Cite
|
Sign up to set email alerts
|

Spherical, Dimpled, and Crumpled Hybrid Colloids with Tunable Surface Morphology

Abstract: Surface morphology is a tool to tune physical properties of colloidal suspensions such as the wettability, viscoelasticity, and depletion attractions. Existing synthesis methods to obtain colloids with a rough surface morphology often result in colloids with nontunable surface properties. Here, we developed a synthetic approach to obtain both spherical and shape-anisotropic hybrid colloids with tunable surface morphology. With our approach, monodisperse linear polystyrene colloids, obtained in large quantities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…have a much higher and frequent variation in curvature. To investigate the effect of large curvature differences, we prepared two batches of polystyrene particles which only differed in their surface roughness and coated them with a silica layer following a Stöber method [33]. In Figure 2 we show that particles with some roughness (A) can be homogeneously coated with a bilayer (B) while particles with very rough surfaces (C) show an inhomogeneous bilayer (D).…”
Section: Materials Zeta Potential [Mv] Homogeneous Mobilementioning
confidence: 99%
“…have a much higher and frequent variation in curvature. To investigate the effect of large curvature differences, we prepared two batches of polystyrene particles which only differed in their surface roughness and coated them with a silica layer following a Stöber method [33]. In Figure 2 we show that particles with some roughness (A) can be homogeneously coated with a bilayer (B) while particles with very rough surfaces (C) show an inhomogeneous bilayer (D).…”
Section: Materials Zeta Potential [Mv] Homogeneous Mobilementioning
confidence: 99%
“…The shape of colloidal particles is one of the most important features that dictates their complex collective behavior. As a result of recent advances in experimental techniques that allow the synthesis of colloidal particles with arbitrary shape and size [1][2][3][4] , it is currently possible to use these particles as building blocks for the selfassembly of complex structures. Colloidal particles are appealing not only for fundamental studies as they are often large enough to allow direct observation of their self-organisation and dynamics, but also for applications as it is their size what makes them suitable candidates for the fabrication of mesoscopic structures that are not easily attainable using molecular systems 5,6 .…”
Section: Self-assembly In Colloidal Systemsmentioning
confidence: 99%
“…1719 Despite the versatility and simplicity of the method, two conflicting mechanisms underlying cavity formation were reported in the current literature. 1721 Huang et al, 17 Cheng et. al, 18 and Xie et.…”
Section: Introductionmentioning
confidence: 99%
“…al 19 and Meester et. al 21 suggested that buckling is the main driving force of the dimple formation.…”
Section: Introductionmentioning
confidence: 99%